Action at a distance: The remarkable coupling of CO 2 uptake to electron transfer in specialized cyanobacterial NDH-1 complexes - Zhifen Zhang; Minquan Zhang; Robert L. Burnap (Proceedings of the National Academy of Sciences, 2025)
Cyanobacteria achieve highly efficient photosynthesis using a CO 2 -concentrating mechanism relying on specialized Type I (NDH-1) complexes. Among these, NDH-1 3 and NDH-1 4 catalyze redox-coupled hydration of CO 2 to bicarbonate, supporting carbon fixation in carboxysomes. The mechanism of coupling electron transfer to CO 2 -hydration by these variant NDH-1 complexes remains unknown. We engineered a Synechococcus PCC7942 strain that expresses exclusively the high flux/low affinity NDH-1 4 complex, enabling the observation of the coupling of CO 2 hydration to cyclic electron flow in isolation from the other NDH-1 isoforms normally present in cells. We found that inhibition of the CupB protein by the carbonic anhydrase inhibitor ethoxzolamide (EZ) suppressed CO 2 uptake, slowed photosystem I rereduction, and abolished proton pumping as probed by acridine orange fluorescence. These effects were absent in strains lacking Cup proteins, confirming specificity. The results demonstrate that CO 2 hydration and electron transfer through NDH-1 4 are tightly coupled via proton translocation across the thylakoid membrane. These findings provide direct evidence for the bidirectional interaction in bioenergetic coupling between the plastoquinone reduction and the CO 2 uptake at the distal Zn-site over a span of ~150 Å and support a proton-removal hypothesis involving the proton transfer pathways from the Zn-site of CO 2 hydration to an energetically coupled proton loading site evolutionarily repurposed from the ancestral proton pumping mechanism to enable energetic CO 2 uptake.